PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN RPP MELALUI SUPERVISI AKADEMIK DI MI AL-KHOIRIYAH WONOLELO PLERET KABUPATEN BANTUL TAHUN 2021 - Subarniyati Subarniyati (Pedir Research Institut, 2022)
Abstract:. This study aims to determine the ability of teachers in preparing lesson plans to prepare learning in the classroom through supervision activities. This research was conducted at MI Al-Khoiriyah Wonolelo Pleret, Bantul Regency. The time required for this classroom action research is about 1 month, from February 10 to March 10, 2021. The subjects of this study were divided into two, namely the subject of the action recipient and the subject who assisted in the research. The subjects who received the action in this study were 14 teachers of MI Al-Khoiriyah Wonolelo Pleret, Bantul Regency, consisting of 6 male teachers and 8 female teachers. This study uses the model developed by Kemis and Taggart. Each action or cycle always consists of four activities: 1) action plan, 2) action implementation, 3) observation or observation, and 4) reflection. In collecting data this Classroom Action Research uses the method of observation, and documentation. While the analysis technique used is descriptive statistical analysis technique. The results of the study indicate that 2. Academic supervision activities carried out by the head of MI Al-Khoiriyah Wonolelo Pleret, Bantul Regency for 14 teachers are activities that can improve the ability and understanding of teachers in preparing lesson plans. Both related to the content and format of the RPP as well as the steps for making the RPP properly and correctly. This can be seen through the supervision activities in each cycle, from cycle 1 which got a score of 34.5 and an average value of 57.5 in the sufficient category, there was a significant increase in the second cycle with a score of 54.7 and a score of 54.7. an average of 91.3 very good category.